Determination of Polycyclic Aromatic Hydrocarbons (PAHs) in Indigowoad Leaves with Preconcentration by Cholesterol-Decorated Nickel Foam (NF) Dispersive Solid-Phase Extraction (DSPE) and Determination by Gas Chromatography–Mass Spectrometry (GC-MS). (13th June 2023) - Xiao, Jing; Chen, Chan; Li, Yang; Fan, Jiahua; Yan, Zhihong; Cai, Ying
Abstract: Cholesterol-coated nickel foam (NF) was prepared by coating with tetraethyl orthosilicate, functionalization with 3-aminopropyltriethoxysilane, and modification with cholesterol. The subsequent characterization was carried out by scanning electron microscopy, X-ray photoelectron spectroscopy, and Fourier-transform infrared spectroscopy. The cholesterol-coated NF was applied as the adsorbent for the dispersive solid-phase extraction of 16 polycyclic aromatic hydrocarbons (PAHs) in the indigowoad leaves traditional Chinese medicine. The primary experimental parameters affecting extraction were investigated with analysis by gas chromatography–mass spectrometry. The limits of detection were from 0.6 to 11.5 ng/mL and the relative standard deviations were from 0.84% to 9.8%. The recoveries were between 69.8% and 149.2%. The developed protocol was employed for the determination of PAHs in traditional Chinese medicines. The total mean concentrations of 16 PAHs, which are priority pollutants, were 1452.04 μg/kg. The most abundant component in indigowoad leaves was acenaphthene (198.23 μg/kg). The results demonstrated that the established method provided favorable performance and the cholesterol-coated NF adsorbent possessed high adsorption properties.